Reclamation of poultry litter for the production of biochar - Rose Kukwa; Donald Kukwa; Samson Barnabas (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Poor management of chicken litter by the poultry industry has caused many environmental issues. Biochar’s unique characteristics make poultry litter-to-biochar conversion an intriguing management option thus, could be utilized as an organic fertilizer for plant nutrients. In this research, poultry litter was converted into biochar, which offers a range of possible applications, including analyzing key nutrients, improving air and water quality, conditioning soil, and neutralizing acidic soils.Method: Fresh poultry litter was pyrolyzed for 20 minutes at a temperature of 500 oC in an oxygen-restricted muffle furnace to produce biochar. The biochar was examined chemically and physically using a variety of techniques. These included microwave plasma atomic emission spectroscopy (MP-AES), the scanning electron microscope (SEM), the Fourier transform infrared (FTIR) spectroscopy, and thermo gravimetric analysis (TGA and DTG).Results: The pyrolysis output was 56.38%, 32.20% ash, 2.00% moisture, 0.60 kg/m3 bulk density, pH 9.65, and 0.00314 dS/m EC. The mineral elemental analysis gave 621.73 mg/kg calcium, 63.65 mg/kg potassium, 48.94 mg/kg magnesium, 13.14 mg/kg sodium, and 11.85 mg/kg phosphorus.  FTIR showed the presence of functional groups which could act as cation adsorbents. SEM pictures showed the sample’s amorphous, non-uniform surface. TGA and DTG curves showed mass loss and sample breakdown as the temperature climbed.Conclusion: Poultry litter converted to biochar can act as a nutrient-rich soil conditioner to address mineral deficits in fruits and vegetables grown in acidic soils. This is a good way to recycle agricultural trash.